2017
DOI: 10.1152/ajpheart.00155.2017
|View full text |Cite
|
Sign up to set email alerts
|

Mineralocorticoid receptor antagonists attenuate exaggerated exercise pressor reflex responses in hypertensive rats

Abstract: Exaggerated heart rate (HR) and blood pressure responses to exercise in hypertension are mediated, in part, by overactivity of the exercise pressor reflex (EPR). The mechanisms underlying this EPR dysfunction have not been fully elucidated. Previous studies have shown that stimulation of mineralocorticoid receptors (MRs) with exogenous administration of aldosterone in normal, healthy rats reproduces the EPR overactivity characteristic of hypertensive animals. Conversely, the purpose of this study was to examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 59 publications
0
13
2
Order By: Relevance
“…The static handgrip exercise with post‐handgrip exercise circulatory arrest, which is an isometric exercise, was performed to assess metaboreflex, along with arm cycling, which is a dynamic exercise, to assess mechanoreflex. The results showed that eplerenone had no significant effects on metaboreflex and mechanoreflex in hypertensive patients; this is inconsistent with previous reports from another group including some of the same authors, 2 which suggested that eplerenone had beneficial effects on exercise pressor reflex in animal models of hypertension. The authors proposed several factors that might account for this discrepancy, including (1) that the dose of eplerenone (average 119.6 mg) used in the current study was too low because it did not significantly lower blood pressure; (2) that the dose sufficient to induce central nervous system (CNS) effects by passing through the blood brain barrier in humans is unknown; and (3) that the potential action of eplerenone on sympathetic nerve activity may be evident only when the renin angiotensin system is activated.…”
contrasting
confidence: 95%
“…The static handgrip exercise with post‐handgrip exercise circulatory arrest, which is an isometric exercise, was performed to assess metaboreflex, along with arm cycling, which is a dynamic exercise, to assess mechanoreflex. The results showed that eplerenone had no significant effects on metaboreflex and mechanoreflex in hypertensive patients; this is inconsistent with previous reports from another group including some of the same authors, 2 which suggested that eplerenone had beneficial effects on exercise pressor reflex in animal models of hypertension. The authors proposed several factors that might account for this discrepancy, including (1) that the dose of eplerenone (average 119.6 mg) used in the current study was too low because it did not significantly lower blood pressure; (2) that the dose sufficient to induce central nervous system (CNS) effects by passing through the blood brain barrier in humans is unknown; and (3) that the potential action of eplerenone on sympathetic nerve activity may be evident only when the renin angiotensin system is activated.…”
contrasting
confidence: 95%
“…(1983) demonstrated that hindlimb muscle stretch did not activate afferents that responded to noxious stimuli, at least in the cat, and the vast majority ( i.e ., >86%) of the muscle afferents that respond to rat hindlimb muscle stretch also respond to hindlimb muscle contraction (Stone, Copp, McCord, & Kaufman, 2015b). Moreover, studies that successfully identify a mechanism that contributes to the generation of the pressor response evoked during rat hindlimb muscle stretch have also found that the same mechanism contributes to the generation of the pressor response evoked during hindlimb muscle contraction (Copp et al., 2016a, b; Downey, Mizuno, Mitchell, Vongpatanasin, & Smith, 2017; Kim & Kaufman, 2019; Leal et al., 2011; McCord, Tsuchimochi, Yamauchi, Leal, & Kaufman, 2011; Nakamoto & Matsukawa, 2008; Schiller et al., 2019; Smith et al., 2005; Smith, Mammen, Mitchell, & Garry, 2003; Tsuchimochi, Yamauchi, McCord, & Kaufman, 2011; Wang, Wang, Patel, Rozanski, & Zucker, 2013; Yamauchi, Stone, Stocker, & Kaufman, 2012). Third, baseline MAP was significantly reduced following EP4‐R blockade in HF‐rEF rats and there was a trend ( P = 0.057) towards a reduction in SHAM rats.…”
Section: Discussionmentioning
confidence: 99%
“…Aldosterone can also activate cell surface MR to promote vasoconstriction via more rapid non-genomic mechanisms [40]. In addition to direct renal and vascular actions, emerging evidence suggests that aldosterone activates brain MR to contribute to sympathetic activation, blood pressure elevation, and augmentation of the exercise pressor reflex in animal models of hypertension and heart failure [23,25,41]. Circulating aldosterone accesses neurons in the brain via MR distributed to circumventricular organs such as the SFO and OVLT, and the hypertensive effects of systemic aldosterone administration are attenuated by lesion of the SFO [23].…”
Section: Aldosteronementioning
confidence: 99%
“…Acute eplerenone also reduces nocturnal blood pressure in primary autonomic failure, implicating a role for MR activation in supine hypertension in these patients [95]. Chronic central MR antagonism lowers blood pressure, reduces efferent sympathetic discharge, and attenuates exaggerated exercise pressor reflex responses in rodent models of hypertension, myocardial infarction, and heart failure ( Table 2) [23,41]. Furthermore, spironolactone enhances cardiac vagal tone and renal baroreceptor reflex sensitivity in rodent models, suggesting improved parasympathetic function.…”
Section: Mineralocorticoid Receptor Antagonistsmentioning
confidence: 99%